2022
DOI: 10.1186/s12889-022-14481-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive capacity of COVID-19-related risk beliefs on weight management behaviors on a commercial weight loss program and speed of COVID-19 vaccination uptake: prospective cohort study

Abstract: Background Recent work has shown that obesity may be a risk factor for severe COVID-19. However, it is unclear to what extent individuals have heard or believe this risk factor information, and how these beliefs may predict their preventive behaviors (e.g., weight management behaviors or COVID-19 preventive behaviors). Previous work has primarily looked at overall risk likelihood perceptions (i.e., not about obesity as a risk factor) within general populations of varying weight and concentrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In contrast with other populations, a study exploring predictors of vaccination often highlights the impact of health-related factors such as obesity, diabetes, hypertension, and smoking on vaccination decisions [26]. However, within the cohort of adults 40+ with coronary heart disease, these factors did not significantly predict vaccination uptake, findings consistent with a US study of the general population that showed that underlying medical conditions or morbid obesity did not influence vaccine decisions [27].…”
Section: Discussionmentioning
confidence: 56%
“…In contrast with other populations, a study exploring predictors of vaccination often highlights the impact of health-related factors such as obesity, diabetes, hypertension, and smoking on vaccination decisions [26]. However, within the cohort of adults 40+ with coronary heart disease, these factors did not significantly predict vaccination uptake, findings consistent with a US study of the general population that showed that underlying medical conditions or morbid obesity did not influence vaccine decisions [27].…”
Section: Discussionmentioning
confidence: 56%
“…For example, recent research found a lack of understanding of the higher risk of COVID for those who are overweight or obese. 14 Participants in the current study did not perceive an elevated susceptibility of COVID-19 due to cancer. While those with certain cancers, including leukemia, have been especially susceptible to SARS-CoV-2, the link between cancer and severe COVID-19 illness and mortality is considerably weaker than that of diabetes, obesity, CVD, and COPD.…”
Section: Discussionmentioning
confidence: 67%